The interface between the theater and to the occupational therapy: reflections on daily life - Ferigollo, Juliana Prestes (2017)
This study sought to identify how theater and Occupational Therapy are in the therapeutic scene aiming to promote health and potency of life of individuals served by this. For this, we created a theater group called “Trials Performing “ that happened at the Federal University of Santa Maria in 2013 and was composed of students aged between 20 and 25 years old. The methodology of action research was used and data analysis was based on content analysis. The results showed that the participants took the group as a place where they could have a moment of reflection on their daily lives, and also that the proposed activities were alternatives to self-knowledge, that is perception of the body, its limits and potential.